Improving the informativeness of Mendelian disease-derived pathogenicity scores for common disease - Samuel S. Kim (Nature Portfolio, 2020)
Pathogenicity scores are instrumental in prioritizing variants for Mendelian disease, yet their application to common disease is largely unexplored. Here, the authors assess the utility of pathogenicity scores for 41 complex traits and develop a framework to improve their informativeness for common disease.